GLOBAL CAPITALISM IN INTERIOR DESIGN OF FAST FOOD RESTAURANTS IN BALI - Artadi, I Made Pande (International Conference on Cultural Studies, 2019)
Food is anything that is eaten and digested in the body, so that it can be useful for physical and spiritual health. Over time, food consumption develops and changes in accordance with changes in human civilization. Economic, information and cultural globalization has affected human eating activities. Cultural contact that transcends geographical, cultural and religious boundaries results in a consumption revolution that is implemented in the form of dining room interior design concepts and restaurant architecture.This research reveals that there has been a consumption revolution in Balinese society. Massively transformed eating activities that previously as an activity to spend value for food, into various forms of pleasure and leisure time. The interior environment of the dining room is arranged not only to fulfill dining activities but to be filled with various forms of fun, entertainment and games. The theoretical approach used in this research is the theory of consumerism from Jean Baudrillard, Adorno and Pierre Bourdeou.The results showed that for some consumers, eating activities are not merely consuming the use value, function value, and its utility, but also to communicate certain meanings contained therein. Modern interior designs in fast food restaurants are used to mark / represent / communicate or send codes of identity and social position in society.